Numerical analysis of an Uppsala University WEC deployment by a barge for different sea states. (1st June 2020) - Chatzigiannakou, Maria Angeliki; Potapenko, Tatiana; Ekergård, Boel; Temiz, Irina
Abstract: Wave energy converters (WECs) have been deployed onshore, nearshore, and offshore to convert ocean wave movement into electricity. The exploitation of renewable energy sources has restrictions; in the case of wave energy, high installation, maintenance, and decommissioning costs have limited their commercial use. Moreover, these offshore operations can be compromised by safety issues. This paper draws attention to offshore operation safety of a WEC developed by Uppsala University. Specifically, this paper investigates what sea states are suitable for the safe deployment of a WEC from a barge. This study follows recommendations in DNV-RP-H103 for analysis of offshore operations, namely lifting through the wave zone. ANSYS Aqwa is used to find hydrodynamic forces acting on a typical barge, using frequency domain analysis. Based on these hydrodynamic simulation results and methodology given in DNV-RP-H103, tables are created to show the sea states that would allow for the safe installation of a WEC using a typical barge. Considered sea states have significant wave heights varying between 0 m and 3 m and the wave zero crossing periods varying between 3 s and 13 s. The WEC submersions are considered between 0 m and 7 m, i.e. when the WEC is in the air until it is fully submerged. Highlights: Hoisting system failure while deploying a wave energy converter from a barge. The study follows DNV-RP-H103 regulations. The hydrodynamic responses of the barge and the WEC are simulated in ANSYS AQWA. A safety operation table is created for safe operational sea states. As the hook lowering velocity rises, the safe operational sea states reduce.